St. Nicholas Collegiate Church, west exterior wall, door, jamb and arch - O'Donovan, Danielle (My University, 2008)
West door that terminates central aisle, centre of three gabled front. Broad splay. Moulding fron intrados comprises: chamfer, hollow, roll-and-fillet, hollow chamfer, roll-and-fillet, hollow chamfer, roll-and-fillet, hollow chamfer, roll-and fillet, hollow, chamfer. The mouldings here are broad, and similar examples of this roll and fillet are only found in other doors at this site.
Door
Keywords: Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Gothic doorways; Collegiate churches; Late Medieval; roll-and-fillet moldings; moldings, hollow